Incapacitated and/or Forcible Rape Experience Predicting College Women's Rape Victim Empathy - Osman, Suzanne L. (Violence against women, 2025)
Rape experience is common and victim empathy may help address it (e.g., prevention, victim support). We examined rape victim empathy based on type of rape experience (none, incapacitated, forcible, combined). Undergraduate women (n = 658) completed the Rape Victim Empathy-During Subscale and Sexual Experiences Survey-Short Form Victimization. Rape experience was associated with greater empathy, especially for those with any forcible experience. Perhaps due to weaker memory of their own rape event, incapacitated victims may be relatively less able than forcible victims to understand another victim's perspective during a rape. Researchers should consider examining incapacitated and forcible rape as distinct experiences.